Symbiotic and agronomic characterization of Bradyrhizobial strains nodulating cowpea in Northern Peru - Valdez, Renzo (2016)
Eighty bacterial strains were isolated from root nodules of cowpea (Vigna unguiculata) plants agriculturally grown in Northern Peru. After isolation, fifty of them reinfected cowpea and eight showed better symbiotic performance than control plants treated with nitrate both under greenhouse and field. Repetitive extragenic palindromic polymerase chain reaction (REP-PCR) clustered the strains into 3 REP-PCR groups. The partial sequence of the 16S rRNA gene from a representative strain of each REP-PCR pattern showed that the strains were closely related to members of genus Bradyrhizobium of the Alphaproteobacteria, but affiliation at the species level was not clear. Pairwise alignments among globally aligned sequences of the 16S rRNA genes, the sequencing of the housekeeping genes atpD, glnII, and recA, and their concatenated phylogenetic analysis showed that strains Rc-391-01 and Rc-458-01 grouped with B. yuanmingense B071T and that strain Rc-352-01 clustered with Bradyrhizobium liaoningense 2281T. Examination of the three representative strains to behave as plant growth-promoting rhizobacteria (PGPRs) showed that none of them solubilized calcium triphosphate and that they all three produced siderophores and IAA-related compounds and had ACC-deaminase activity.